STRATEGI PENYELESAIAN KONFLIK PENGUASAAN LAHAN DI LOKAPURNA TAMAN NASIONAL GUNUNG HALIMUN SALAK - Prasasti, Bayu Gagat; Basuni, Sambas; Sunarminto, Tutut (Media Konservasi, 2016)
The issue of land in Lokapurna caused by the determination of the area became a national park but there are communities in Lokapurna before there was an expansion of the National Park. This study aims to measure and compare the perception among stakeholders in Lokapurna, Measure and compare important value land tenure in lokapurna, formulated the strategies of land tenure conflict resolution at Lokapurna. The land tenure conflict in Lokapurna is caused due to a difference in perception between community with a national park management. The community was not involved when the expansion of the area because national park management feel did not have authority to conduct the review prior to the Minister of forestry Decree No. 175 in 2003. There are four alternative strategies for conflict resolution of land tenure in the Lokapurna, moving out the community as a whole from national park (relocation), developing tourism in Lokapurna, optimizing Lokapurna as a special zone and performing collaborative cooperation between TNGHS management with the community. Keywords: conflict, land tenure, National Park, perception, strategies